Optical Coherence Tomography and Coherence Techniques III 2007
DOI: 10.1364/ecbo.2007.6627_54
|View full text |Cite
|
Sign up to set email alerts
|

Mueller Coherency matrix method for contrast image in tissue polarimetry

Abstract: In this work, we propose the use of the Mueller Coherency matrix of biological tissues in order to increase the information from tissue images and so their contrast. This method involves different Mueller Coherency matrix based parameters, like the eigenvalues analysis, the entropy factor calculation, polarization components crosstalks, linear and circular polarization degrees, hermiticity or the Quaternions analysis in case depolarisation properties of tissue are sufficiently low. All these parameters make in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Therefore, we can assume that the diattenuation effects of the sample are negligible, and the diattenuation information is not useful to improve the image contrast in this case. This result is in agreement with other studies in the literature , where most polarimetric analyses dealing with biological tissues focusses on retardance and depolarization.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Therefore, we can assume that the diattenuation effects of the sample are negligible, and the diattenuation information is not useful to improve the image contrast in this case. This result is in agreement with other studies in the literature , where most polarimetric analyses dealing with biological tissues focusses on retardance and depolarization.…”
Section: Resultssupporting
confidence: 93%
“…Different polarimetric studies of biological samples have shown that retardance and depolarization are the main polarimetric channels providing significant information of tissues . In addition, the information of samples encoded in the polarization of light strongly depends on the particular structure to be analyzed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation